Profesionalisme Guru dalam Proses Pembelajaran di Madrasah Ibtida’iyah - Munawir, Munawir; Cholifah, Nur; Bela, Maulida Salsa (Lembaga Yasin AlSys, 2025)
This research is motivated by the limited studies on teacher professionalism in the learning process at the Madrasah Ibtida'iyah level, even though this phenomenon has a significant impact on the quality of basic education and student learning outcomes. The purpose of this study was to explore teachers' understanding of professionalism, professional practices in learning, and supporting and inhibiting factors. The method used was a qualitative approach with a case study design, with a sample of six teachers from two Madrasah Ibtida'iyah selected through purposive sampling techniques. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using thematic analysis techniques. The results showed that teachers' understanding of professionalism was still limited to normative aspects such as discipline and administrative responsibility; professional practices were also greatly influenced by institutional support, training, and leadership of the madrasah principal. This finding is in line with the research objectives and strengthens Mulyasa's theory of teacher competence, that professionalism is the result of the interaction between personal competence and institutional support. The main conclusion of this study is the importance of the role of the madrasah principal and the work ecosystem in developing teacher professionalism holistically. The implications of this study include theoretical aspects, such as enriching the literature on teacher professionalism in the context of madrasah education, as well as practical aspects, namely the need to strengthen institutional capacity and contextual training for teachers. This study also opens up opportunities for further studies on professionalism improvement models based on the development of teacher learning communities.